Penerapan Bimbingan Kelompok dengan Teknik Peer Group untuk Meningkatkan Kemampuan Remaja dalam Menjalin Persahabatan - Retno Tri Hariastuti (Jurnal Psikologi Teori dan Terapan, 2012)
This study was conducted to examine the effectiveness of group guidance with peer group technique to improve friendship-making ability among adolescents who live in an orphanage institution. An experimental method with one group pre-test and post-test design was used. Forty young female teenagers who lived in Khoiriyah Hasyim orphanage institution in Surabaya were involved in the experiment. The subjects were chosen based on the pre-survey data collected using a questionnaire that shows the lack of their abilities in making friendship. Data were analysed using t-test. The result suggested that group guidance with peer group technique can improves adolescents’ friendship-making ability in the context of orphanage environments.